Do the competitions played during congested weeks influence the external load of Spanish soccer teams? Analysis by match playing time - Lobo-Triviño, D.; García-Calvo, T.; Polo-Tejada, J.; Raya-González, J.; López del Campo, R.; Resta, R.; Vasquez-Bonilla, A. A. (Sports Medicine - Open, 2026)
Background This study aimed to examine differences in external load among professional soccer players during congested weeks across different competition types (League, Cup, and Champions League (UCL)), considering individual match playing time. A retrospective, descriptive, and longitudinal analysis was conducted using external load data from 120 players belonging to the top five teams in the Spanish LaLiga during the 2023/24 season, including 2,671 match observations. Players were categorised by playing time (Starters, Replaced, Fringe, and Non-Starters), and weeks were classified as non-congested (NCON) or congested (CON), with further distinction by competition type. External load metrics were recorded using the Mediacoach® tracking system and analysed through Linear Mixed Models.